A Protocol to Study Mitochondrial Function in Human Neural Progenitors and iPSC‐Derived Astrocytes. Issue 1 (2nd September 2020) - Assis‐de‐Lemos, Gabriela; Ledur, Pítia Flores; Karmirian, Karina; Rehen, Stevens Kastrup; Galina, Antonio
Abstract: Mitochondrial dysfunction is a central component in the pathophysiology of multiple neuropsychiatric and degenerative disorders. Evaluating mitochondrial function in human‐derived neural cells can help characterize dysregulation in oxidative metabolism associated with the onset of brain disorders, and may also help define targeted therapies. Astrocytes play a number of different key roles in the brain, being implicated in neurogenesis, synaptogenesis, blood‐brain‐barrier permeability, and homeostasis, and, consequently, the malfunctioning of astrocytes is related to many neuropathologies. Here we describe protocols for generating induced pluripotent stem cell (iPSC)−derived astrocytes and evaluating multiple aspects of mitochondrial function. We use a high‐resolution respirometry assay that measures real‐time variations in mitochondrial oxygen flow, allowing the evaluation of cellular respiration in the context of an intact intracellular microenvironment, something not possible with permeabilized cells or isolated mitochondria, where the cellular microenvironment is disrupted. Given that an impairment in the mitochondrial regulation of intracellular calcium homeostasis is involved in many pathologic stresses, we also describe a protocol to evaluate mitochondrial calcium dynamics in human neural cells, by fluorimetry. Lastly, we outline a mitochondrial function assay that allows for the measurement of the enzymatic activity of mitochondrial hexokinase (mt‐HK), an enzyme that is functionally coupled to oxidative phosphorylation and is involved in redox homeostasis, particularly in the brain. In all, these protocols allow a detailed characterization of mitochondrial function in human neural cells. High‐resolution respirometry, calcium dynamics, and mt‐HK activity assays provide data regarding the functional status of mitochondria, which may reflect mitochondrial stress or dysfunction. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Generation of iPSC‐derived human astrocytes Basic Protocol 2 : Measuring real‐time oxygen flux in human iPSC‐derived astrocytes using a high‐resolution OROBOROS Oxygraph 2k (O2k) Basic Protocol 3 : Measuring mitochondrial calcium dynamics fluorometrically in permeabilized human neural cells Basic Protocol 4 : Measuring OXPHOS‐dependent activity of mitochondrial hexokinase in permeabilized human neural cells using a spectrophotometer